2017
DOI: 10.31482/mmsl.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICALLY ACTIVE COMPOUNDS OF KNOTWEED (Reynoutria spp.)

Abstract: Knotweeds (Reynoutria Houtt.) are plants native to the Far East. Japanese knotweed was introduced from Japan to the unsuspecting West by the horticultural activities of Philippe von Siebold via his nursery at Leiden in the 1840s. By 1854, the plant had arrived at the Royal Botanic Gardens in Edinburgh. The plants were then sold by a large number of commercial nursery gardens around the country. Further vegetative spread followed naturally along watercourses. The knotweed is currently extremely persistant invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 110 publications
(105 reference statements)
0
23
0
1
Order By: Relevance
“…There is, however, also a beneficial side to knotweeds. Their flower is an important source of nectar for honeybees [10], they accumulate heavy metals from contaminated soil in their leaves and stems, and their huge biomass can be used as raw material within the paper production industry [10,11]. Knotweeds have been used in traditional Chinese medicine for decades as laxatives and food.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, also a beneficial side to knotweeds. Their flower is an important source of nectar for honeybees [10], they accumulate heavy metals from contaminated soil in their leaves and stems, and their huge biomass can be used as raw material within the paper production industry [10,11]. Knotweeds have been used in traditional Chinese medicine for decades as laxatives and food.…”
Section: Introductionmentioning
confidence: 99%
“…Reynoutria species (knotweed) are medicinal plants that belong to the family Polygonaceae and are widely distributed in eastern Asia, North America and Europe. The Reynoutria species are perennial herbs with thickened, long-branched rhizomes [1,2]. Some species have been used as food resources or traditional folk medicines for treating conditions such as neuro-cardiovascular diseases, constipation [1], inflammation, jaundice [2], hyperlipidemia and skin burns [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The only differences are its smaller size, red flower and seeds [11]. Early works have reported many phytochemical constituents from the roots and leaves of Reynoutria species, including stilbenes (resveratrol and polydatin), flavonoids (rutin, apigenin, quercetin, quercitrin, isoquercitrin, hyperoside, reynoutrin and kaempferol), anthraquinones (emodin, citreorosein, physcion, fallacinol, chrysophanol, phylloquinones B and C, and anthraglycosides A and B), coumarins, essential oils, and others (lapathoside, 8-hydroxycalamenene, oleanolic acid, chlorogenic acid, protocatechuic acid, gallic acid, tachioside etc) [1][2][3][4][8][9][10][14][15][16].Although Reynoutria species are used as a folk medicine, their exact botanical origin is unclear. Previous studies have reported certain Reynoutria species with great ambiguity in their taxonomic classification, because of variabilities in their chromosome number and morphology [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reynoutria japonica Houtt., Japanese knotweed, is a medicinal plant and belongs to the Polygonaceae family. As a native perennial herb, it is mainly grown in Korea, Japan, China, and North America [17,18,19]. Furthermore, the roots of this plant are traditionally used for medicinal purposes in the treatment of inflammation, infection, jaundice, and hyperlipidemia diseases [20].…”
Section: Introductionmentioning
confidence: 99%